How polarization, populist attitudes, and cultural backlash affect citizens’ support for democracy: Evidence from Spain - Irene Palacios Brihuega; Antonio Garrido Rubia; Antonia Martínez Rodríguez (Revista Internacional de Sociología)
ABSTRACT